Five-year trend analysis of malaria prevalence at Pawe General Hospital, Northwest Ethiopia, from 2020 to 2024 - Habtamu Amsalu; Abayeneh Girma (Medicine, 2026)
Globally, malaria remains a major public health challenge caused by Plasmodium species and is transmitted through the bite of the female Anopheles mosquito. Monitoring trends in malaria prevalence is crucial for effective disease control and prevention. Thus, this study aimed to assess the five-year trend of malaria prevalence at Pawe General Hospital (PGH) in northwest Ethiopia from 2020 to 2024. A retrospective review of laboratory registration logbooks was conducted to analyze malaria blood film examination results. The STROBE statement was followed to report the current study. Data were collected via a standardized extraction tool and entered into SPSS version 26 for analysis. Descriptive statistics summarized the sociodemographic characteristics of the study participants. Binary logistic regression was employed to evaluate associations between malaria prevalence trends and factors such as sex, age, year, and season. Among the 94,646 blood samples examined, 18,860 (19.9%) were microscopically confirmed to be positive for malaria parasites. Among the confirmed cases, Plasmodium falciparum accounted for 13,680 (72.5%), whereas Plasmodium vivax accounted for 5627 (27.5%). Throughout the study period, P falciparum was the predominant species. Compared with 2024, the odds of malaria prevalence were 1.53, 1.13, 1.28, and 0.96 times higher in 2020, 2021, 2022, and 2023, respectively. Males were approximately 1.13 times more likely to contract malaria than females. Compared with individuals over 45 years of age, the odds of malaria prevalence were 1.21 times greater in children under 5 years of age, 1.35 times greater in those aged 5–14 years, and 1.61 times greater in those aged 15–45 years. The prevalence of malaria varied significantly across seasons, with the highest peak recorded in autumn. Although the malaria prevalence rate in the study area declined substantially between 2020 and 2024, the overall prevalence remains a significant public health concern, necessitating additional interventions to achieve further reductions. To meet Sustainable Development Goal (SDG) 3 on good health and well-being, particularly target 3.3, which aims to end malaria, stakeholders and policymakers must prioritize expanding the distribution of insecticide-treated bed nets, implementing educational campaigns, and providing targeted support for vulnerable groups to reduce malaria prevalence and improve overall health outcomes.